Examining the Relationship Between Academic Stress, Maladaptive Perfectionism and Trauma-Related Responses Among University Students - Archie Kapoor; Rita Kumar (International Journal of Education Sciences, 2025)
Academic stress is a significant concern among university students, frequently contributing to maladaptive perfectionism and trauma-like responses. While perfectionism can enhance performance, its maladaptive variant may be exacerbated by academic stress which can induce trauma-like responses. This study investigates the correlation between academic stress, maladaptive perfectionism and trauma-like responses. Validated self-report measures were used in a quantitative, correlational study involving 101 university students. Linear regression analysis and Kendall’s Tau-B correlation were used because of non-normal data distribution. The results showed that maladaptive perfectionism and academic stress were significantly correlated (τ= 0.315, p< 0.001). The strongest correlation was found between academic stress and parental expectations & criticism (τ= 0.342, p< 0.001). There was a weak yet significant correlation between trauma-like responses and maladaptive perfectionism (τ= 0.149, p= 0.030), while trauma-like responses correlated significantly with academic stress (τ= 0.148, p= 0.032). These relationships were further corroborated by regression analysis, which showed that the model explained 22.9% of the variation (R2= 0.229, F (2, 97) = 14.4, P< 0.001). The findings underline the necessity of focused interventions in academic contexts by demonstrating the substantial influence of academic stress on maladaptive perfectionism as well as trauma-like responses.
Keywords: Academic stress; Maladaptive Perfectionism; Parental expectations; Trauma-related responses